The Effect of the RADEC Learning Model on the Reading Literacy of Fifth Grade Students at Cijeruk Elementary School - Pujiasih, Yunita; Sopandi, Wahyu; Hendriawan, Deri; Permatasari, Anita (International Conference on Elementary Education, 2025)
The low reading literacy skills of elementary school students remain a serious issue in Indonesian education. Observations at SDN Cijeruk reveal that most fifth-grade students struggle to identify main ideas, make inferences, and understand implied meanings in reading texts. This condition highlights the need for a learning model that fully engages students in the reading process. This study aims to analyze the effect of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on improving the reading literacy of fifth-grade students at SDN Cijeruk. The research employed a quasi experimental method with a nonequivalent control group design. A total of 68 students participated, divided into an experimental class (34 students) applying the RADEC model and a control class (34 students) using conventional learning. Data were obtained through pretest and posttest reading literacy assessments and analyzed using a t-test. The results showed a significant improvement in the experimental class, with a mean posttest score of 83.47 compared to 75.12 in the control class (tcount = 3.42 > ttable = 2.00). These findings indicate that the RADEC model effectively enhances students’ reading comprehension skills. The novelty of this study lies in its application of the RADEC model to strengthen reading literacy in a rural elementary school context an area that has received limited attention in prior RADEC-based literacy research. The model fosters critical thinking, collaborative discussion, and deeper text comprehension among students.